An evidence-based scale for the antecedents of depressive symptoms in Australian adults. (October 2016) - Liu, Xin; Furuya-Kanamori, Luis; Siskind, Dan; Crompton, David; Williams, Gail M; Kostner, Karam; Vitetta, Luis; Doi, Suhail A
Objective: To develop and test a self-reported scale designed to measure the antecedents of depression. Methods: Participants of the Sustainable Mastery of Innovative Lifelong Exercise (SMILE) Tai Chi program were invited to complete the scale for antecedents of depressive symptoms. The scale included questions regarding events/factors the participants have experienced over the past three months and preceded their depressive symptoms. The reliability of the questions was assessed using the Cronbach's alpha. Principal components analysis was used to examine if there were domains of interest across the scale questions. Results: A total of 126 participants completed the scale. The scale had a good internal consistency (Cronbach's α = 0.82). Principal components analysis identified three components (life events, psychosocial problems, and physical/health problems) in the scale and the components detected the root categories of depression in more than 56% of the cases. Conclusions: This simple self-administered scale has proven to provide a reliable measure for the antecedent factors of depression in the SMILE Tai Chi cohort; further validation of the scale in different settings is encouraged.